THE STYLISTICS OF HUMOR IN CONTEMPORARY LITERATURE (FAN, TA’LIM, TEXNOLOGIYA VA ISHLAB CHIQARISH INTEGRATSIYASI ASOSIDA RIVOJLANISH ISTIQBOLLARI, 2025)
This article explores the stylistics of humor in contemporary literature, examining how modern authors employ various techniques to create humor that entertains, critiques, and reflects on societal issues. It covers key stylistic elements such as irony, wordplay, exaggeration, parody, and dark humor, highlighting how these tools are used to deepen the narrative and engage readers. The article also discusses how cultural and social contexts shape the humor found in contemporary works, particularly in relation to identity, politics, and technology. Ultimately, the article demonstrates that humor in contemporary literature is not only a source of amusement but also a powerful means of exploring complex themes and connecting with readers on a deeper level.